2005
DOI: 10.1254/jphs.fp0050353
|View full text |Cite
|
Sign up to set email alerts
|

Novelty Stress Increases Fecal Pellet Output in Mongolian Gerbils: Effects of Several Drugs

Abstract: Abstract. Stress-induced colonic functional changes have been investigated mainly under conditions involving physical stress, like in the restraint stress model. In this study, we established a new stress-induced defecation model involving the placement of Mongolian gerbils in a novel environment (novelty stress) and determined the effects of several drugs on novelty stress-induced fecal pellet output. When animals kept in groups were placed individually in small cages, the fecal pellet output markedly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…gut passage time). Several studies have shown that colonic function can be increased through stress-induced changes and function may also be altered with exposure to different stressors (Stam, Akkermans & Wiegant, 1997;Okano, Nagaya & Inatomi, 2005). In other small mammals, where feces were collected every 2-4 h, changes in adrenocortical activity have also been detected in FCM concentrations within 12 h [e.g.…”
Section: Discussion Validationmentioning
confidence: 99%
“…gut passage time). Several studies have shown that colonic function can be increased through stress-induced changes and function may also be altered with exposure to different stressors (Stam, Akkermans & Wiegant, 1997;Okano, Nagaya & Inatomi, 2005). In other small mammals, where feces were collected every 2-4 h, changes in adrenocortical activity have also been detected in FCM concentrations within 12 h [e.g.…”
Section: Discussion Validationmentioning
confidence: 99%
“…Furthermore, the report showed that anti-muscarinic agents, which inhibited normal defecation in rats in our present study, exerted no or slight inhibitory effects on MMC cycle length, suggesting that the inhibitory effect of alosetron on the MMC cycle length did not indicate those on normal defecation in rats. Although the effects of ramosetron and alosetron on normal defecation in rats were not actually evaluated in these two literature reports, Okano et al (9) reported that alosetron significantly inhibited both novelty stress-induced defecation and normal defecation in Mongolian gerbils. However, we also obtained the data showing that oral administration of ramosetron did not inhibit normal defecation in dogs, whereas tiquizium significantly inhibited it (24).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical study of Bearcroft et al (7) showed that the postprandial plasma concentration of 5-HT in IBS patients was higher than that in healthy volunteers. Furthermore, 5-HT 3 -receptor antago-nists have been reported to inhibit stress-induced abnormal defecation in animals (8,9), suggesting the involvement of 5-HT 3 receptors in the pathogenesis of IBS.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to one hour of WAS caused an increase in fecal pellet output compared to sham controls in rats [48] and in Mongolian gerbils [49]. This propulsive activity was induced by myenteric cholinergic neurons located in the colon, as demonstrated by increased expression of the neuronal transcription factor c-Fos, a marker of neuronal activation [50].…”
Section: Motilitymentioning
confidence: 96%